Macrolide susceptibility and serotype specific macrolide resistance of invasive isolates of Streptococcus pneumoniae in Germany from 1992 to 2008 - Mutscher Christina; Reinert Ralf; Imöhl Matthias; van der Linden Mark (BMC Microbiology, 2010)
Abstract Background Macrolide resistant Streptococcus pneumoniae has been on a gradual increase in Germany for over a decade. The current study was undertaken against the background of the recent observation of declining macrolide resistance rates especially among German children. Nationwide surveillance of invasive pneumococcal disease has been conducted in Germany since 1992. A population- and laboratory-based approach was used to collect data on invasive pneumococcal disease, and isolates sent to the National Reference Center for Streptococci by diagnostic microbiological laboratories from 1992 to 2008 were included in this study. Results From 1992 to 2008, data on macrolide susceptibility were available for 11,807 invasive isolates. 8,834 isolates (74.8%) were from adults (≥ 16 years), and 2,973 isolates (25.2%) from children (< 16 years). The overall nonsusceptibility rate of all isolates was 16.2% (intermediate, 0.2%; resistant, 16.0%). Higher resistance rates were observed among children (intermediate, 0.2%; resistant, 23.8%) than among adults (intermediate, 0.3%; resistant 13.4%). Maximum nonsusceptibility rates during the period under study were observed in 2005 (children: intermediate, 0.3%; resistant, 32.3%; adults: intermediate, 0.0%; resistant, 18.6%), while nonsusceptibility rates in 2008 were considerably lower, especially for children (children: intermediate, 0.0%; resistant, 15.2%; adults: intermediate, 0.1%; resistant, 12.9%). The rate of resistance was higher among the vaccine serotypes (7-valent, 36.6%; 10-valent, 28.2%; 13-valent, 24.3%) than among the non vaccine serotypes (non 7-valent, 6.5%; non 10-valent, 7.4%; non 13-valent, 6.3%). Serotype 14 (69.6% nonsusceptibility) proved to be the most resistant serotype. Conclusions There has been a considerable and statistically significant decrease in macrolide nonsusceptibility in Germany since 2005, especially among children.